Unraveling cutaneous histiocytosis: insights into histology, pathogenesis, diagnosis, and treatment pitfalls - Scurtu, Lucian G.; Scurtu, Francesca; Simionescu, Olga (Frontiers in Medicine, 2025)
Histiocytoses represent a group of diverse rare disorders characterized by the abnormal accumulation of cells derived from the mononuclear phagocyte system in various tissues and organs. The mononuclear phagocyte system includes monocytes, macrophages, dendritic cells, and specialized tissue-resident phagocytes. These cells are essential for both innate and adaptive immunity and preserving tissue homeostasis. Several classifications of histiocytoses by the Histiocyte Society (1987, 1997, 2016) and WHO (2018, 2022) and an International Consensus Classification (2022) are generally acknowledged. The WHO 2022 classification clarifies these heterogeneous disorders by dividing them into three major groups. Cutaneous involvement in histiocytosis is often polymorphous, making clinical decision more challenging. Cutaneous histiocytoses can occur either as primary cases or as a manifestation of a multisystemic disease. In support of the standard pathology report, immunohistochemical staining is warranted. The exact etiopathogenesis of histiocytoses remains poorly understood, and various associations with malignancies, including visceral and hematologic cancers, as well as autoimmune diseases and infections (Borrelia burgdorferi) are still under review. One of the most recent advancements in this field is the discovery of somatic mutations in the RAF-MEK-ERK signaling pathway, particularly BRAF mutations. Oncogene-induced senescence-associated BRAF mutations have been described in Langerhans cell histiocytosis and Erdheim-Chester disease. Targeted therapies with BRAF inhibitors such as dabrafenib and vemurafenib have shown promising results. MEK inhibitors, like trametinib and cobimetinib, have demonstrated efficiency regardless of the BRAF mutation status. Local treatments of cutaneous histiocytosis include topical steroids, calcineurin inhibitors, alkylating agents, phototherapy, steroid injections, and laser therapies. Despite the current advances in pathogenesis and treatments, cutaneous histiocytosis stands as a challenging and heterogeneous group of disorders, and treatment guidelines are warranted.